Peran Strategis Lembaga Keuangan Syariah dalam Peningkatan Ekonomi dan Pemberdayaan Masyarakat - Aida Ulviani Nst; Marliyah Marliyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the strategic role of Sharia Financial Institutions (LKS) in supporting economic growth and community empowerment in Medan City. Using a qualitative approach, this study highlights the contribution of LKS in empowering micro, small, and medium enterprises (MSMEs), increasing Islamic financial literacy, and financial inclusion. Results show that LKS have an important role in strengthening the community's economy despite facing challenges such as lack of literacy, limited digital services, and minimal government support. Development strategies include improving accessibility, socialization, product innovation, and government policy support. The findings confirm the importance of strengthening the role of LKS to encourage sustainable sharia-based economic growth in Medan City.